Performance characteristics of GaInP/InGaAs/Ge triple-junction photovoltaic panels for near-space vehicles via ground experiments. (15th November 2022) - Hu, Jianhui; Li, Yipo; Chen, Wujun; Gao, Chengjun; Gao, Jifeng; Zhang, Yibei; Qiu, Zhenyu
Highlights: Indoor tests of solar irradiance, tilt angle and wind velocity are performed. Photovoltaic voltage reaches the maximum value at 200 W/m 2 and changes slightly. The effect of insulation layers on temperature reduction is remarkable. The effect of wind velocity on current and temperature is small after 5.3 m/s. Abstract: The utilization of GaInP/InGaAs/Ge triple-junction photovoltaic panels to convert solar energy for meeting long duration energy demands of near-space vehicles has attracted considerable attention due to the abundant solar irradiance and high conversion efficiency of the photovoltaic (PV) panels. The basic electrical and thermal performance of such PV panels in relation to the near-space environment is indispensable for designing the cruising duration and guaranteeing the structural safety. For these reasons, the essential environment factors need to be simulated and quantified under the controlled experimental conditions. Taking the operating conditions of the near-space vehicles into consideration, the solar irradiance, tilt angle and wind velocity are the major influencing factors. This paper thus performs a series of ground experiments to identify typical observations and determine critical values. The experimental results show that a maximum voltage of GaInP/InGaAs/Ge triple-junction photovoltaic panels is reached at a solar irradiance of 200 W/m 2 and this voltage keeps almost stable with the varying factors. For the effects of solar irradiance, the current and temperature of the photovoltaic panels increase linearly with the solar irradiance rise. It is obtained that the PV current and temperature change with tilt angle increase and the maximum voltage exists at the angle of 45°. It is clear that the effects of wind velocity on the current and temperature of the photovoltaic panels tend to be small after a critical value (5.3 m/s).